The cell surface and its metabolism. - Crumpton, M; Owens, R; Gallagher, C; Davies, A (1983)
The cell surface structure is highly dynamic. In particular, binding of ligand induces the redistribution of receptors on the cell surface as well as the internalisation of ligand-receptor complexes. Internalisation in turn leads to a recycling of the receptor or to a decrease in the cell's responsiveness to the ligand. Modulation of the cell surface structure is apparently regulated intracellularly by components of the cell's cytoskeleton. A crucial component in this respect is likely to be a sub-membranous filamentous network that is linked directly to the cytoplasmic face of the surface membrane. In erythrocytes this network can be separated from purified preparations of the plasma membrane by virtue of its insolubility in nonionic detergents. Application of this procedure to the plasma membrane fraction of human B lymphoblastoid cells has yielded a detergent-insoluble residue comprising actin and a 68,000-Mr polypeptide as major components, together with polypeptides of 28,000-, 33,000- and 120,000-Mr as prominent but more minor components. The association of the 68,000-Mr protein with the detergent-insoluble residue and the original plasma membrane is Ca2+-dependent. Burkitt lymphoma cells differ noticeably from lymphoblastoid cells in that the 68,000-Mr protein is not associated with the inner face of the surface membrane. This difference may reflect the malignant phenotype of Burkitt lymphomas or the hypothetical sub-population of normal B lymphocytes from which the lymphomas are derived.